2007
DOI: 10.1002/cncr.22864
|View full text |Cite
|
Sign up to set email alerts
|

Patient survival by Hsp70 membrane phenotype

Abstract: BACKGROUNDHeat shock proteins (HSPs) play important roles in tumor immunity. The authors prospectively investigated the correlation between the tumor‐specific Hsp70 membrane expression as an independent clinicopathological marker and overall survival in tumor entities that differ in their route of metastasis.METHODSHsp70 membrane expression was examined by flow cytometry in 58 colon, 19 gastric, 54 lower rectal carcinoma, and 19 squamous cell carcinoma specimens and the corresponding normal tissues at time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 46 publications
(53 reference statements)
1
53
0
Order By: Relevance
“…These findings might be explained by the fact that membrane Hsp70 might facilitate metastases, support adherence of tumor cells to endothelial cells and organs, or might confer resistance to an unfavorable milieu during metastasis. In line with these findings we could show that overall survival of patients with membrane Hsp70-positive squamous cell carcinomas of the lung and lower rectal carcinomas was significantly reduced compared to those patients with membrane Hsp70-negative tumors (Pfister et al, 2007). Apart from solid tumors also bone marrow samples of patients suffering from acute (AML) and chronic (CML) myeloid leukemia are frequently membrane Hsp70-positive (Gehrmann et al, 2003).…”
Section: Heat Shock Proteins and Tumorigenesissupporting
confidence: 58%
“…These findings might be explained by the fact that membrane Hsp70 might facilitate metastases, support adherence of tumor cells to endothelial cells and organs, or might confer resistance to an unfavorable milieu during metastasis. In line with these findings we could show that overall survival of patients with membrane Hsp70-positive squamous cell carcinomas of the lung and lower rectal carcinomas was significantly reduced compared to those patients with membrane Hsp70-negative tumors (Pfister et al, 2007). Apart from solid tumors also bone marrow samples of patients suffering from acute (AML) and chronic (CML) myeloid leukemia are frequently membrane Hsp70-positive (Gehrmann et al, 2003).…”
Section: Heat Shock Proteins and Tumorigenesissupporting
confidence: 58%
“…Recent studies confirmed that a reduction or depletion of hepatic NK cells could enhance tumor growth in the liver (19), whereas enhanced NK activity contributed to reduced liver metastases in several tumor models (20,21). Moreover, indirect evidence suggests that susceptibility of human cancer cells to NK-mediated immune attack can affect their ability to generate liver metastases (22).…”
Section: Cells Of the Hepatic Sinusoid Can Kill Tumor Cellsmentioning
confidence: 97%
“…This membrane form of Hsp70 is widely expressed on cultured cancer cells, including leukemic cells [23], [24], lung [12], colorectal [16], [25], and breast cancer cells [19]. Furthermore, an ongoing screening program which currently includes the analysis of primary tumors from over 1,000 patients has demonstrated that this membrane form of Hsp70 is also present on approximately 50% of all tumor entities tested, including leukemia [26], [27], melanoma [28], gastrointestinal [25] and breast tumors [29].…”
Section: Introductionmentioning
confidence: 99%